2018
DOI: 10.25115/ejrep.v16i45.2101
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la Aplicación de Programas de Alto Rendimiento para alumnos con altas Capacidades

Abstract: Introducción. Esta investigación se enfoca en proporcionar un proyecto para estudiantes dotados con programas de enriquecimiento que se pueden realizar a nivel escolar.Método. Para lograr esto, se diseñaron los programas, se capacitó a los maestros en seis centros educativos, se seleccionaron 37 estudiantes dotados y se aplicaron pruebas de atención (D2); Se aplicaron pruebas de creación (PIC y CREA) y Habilidades cognitivas para resolver problemas interpersonales (Evhocospi) antes y después de la ejecución de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Gifted students need projects involving intellectual, creative, and cooperative challenges (Martin-Lobo et al, 2018). They prefer complex extracurricular subjects, authentic knowledge, real problems that require making connections between ideas, and selecting the format of the products of their learning; however, they also choose to work in teams with other students for part of the time (Kanevsky, 2011).…”
Section: Programs For Gifted Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gifted students need projects involving intellectual, creative, and cooperative challenges (Martin-Lobo et al, 2018). They prefer complex extracurricular subjects, authentic knowledge, real problems that require making connections between ideas, and selecting the format of the products of their learning; however, they also choose to work in teams with other students for part of the time (Kanevsky, 2011).…”
Section: Programs For Gifted Studentsmentioning
confidence: 99%
“…Most intervention programs for gifted students have focused on academic outcomes or cognitive variables (Memmert, 2006;Kuo et al, 2010;Welter et al, 2018); only a small number have focused on psychosocial aspects (Neihart, 2007). Enrichment programs can improve not only students' academic performance (Aljughaiman, 2011;Golle et al, 2018) or motivation (Gubbels et al, 2014) but also their self-concept (Feldhusen et al, 1990;Gubbels et al, 2014), same-sex and opposite-sex relationships (Rinn, 2006), and interpersonal problem solving (Martin-Lobo et al, 2018). They have been shown to be effective in both primary (e.g., Feldhusen et al, 1990;Gubbels et al, 2014;Kim, 2016;Martin-Lobo et al, 2018) and secondary schools (e.g., Rinn, 2006;Aljughaiman, 2011;Fraleigh-Lohrfink et al, 2013;Sastre-Riba, 2013;Singh, 2013).…”
Section: Programs For Gifted Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tener una definición precisa de altas capacidades es un tanto difícil, pues hay diversos conceptos que se refieren a una misma entidad. Si bien hay muchos enfoques para definir al alumnado más capaz, se puede conceptualizar la alta capacidad como una potencialidad intelectual elevada y configurada multidimensionalmente, lo que lleva a que la persona tenga un funcionamiento cognitivo elevado (Sastre-Riba, 2008) y por ende necesita recibir una respuesta educativa específica para el desarrollo de sus potencialidades (Martín-Lobo et al, 2018).…”
Section: Introductionunclassified
“…Use of a multidimensional psycho-educational model focusing on the common characteristics of gifted students on programs implemented in academic contexts [14] indicated that the specific skills that enabled them to acquire knowledge more easily than the rest of their peers according to Renzulli's [15] consolidated three ring model included the three inter-related dimensions considered present in gifted people; higher general intelligence, high general motivation, and high levels of creativity. A combination of the three dimensions would yield optimum performance and success.…”
Section: Introductionmentioning
confidence: 99%